Trade, Standards, and Poverty: Evidence from Senegal - Miet Maertens; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
An emerging literature on standards, global supply chains, and development argues that enhanced quality and safety standards are major trade barriers for developing country exports and cause the marginalization of small businesses and poor households in developing countries. This paper is the first to quantify income and poverty effects of such high-standards trade and to integrate labor market effects, by using company and household survey data from the vegetable export chain in Senegal. First, horticultural exports from Senegal to the EU have grown sharply over the past decade, despite strongly increasing food standards in the EU. Second, these exports have strong positive effects on poor households?income. We estimate that these exports reduced regional poverty by around 12 percentage points and reduced extreme poverty by half. Third, tightening food standards induced structural changes in the supply chain including a shift from smallholder contract-based firming to large-scale integrated estate production. However, these changes mainly altered the mechanism through which poor households benefit: through labor markets instead of product markets. Moreover, the impact on poverty reduction is stronger as the poorest benefit relatively more from working on large-scale firms than from contract firming. These findings challenge several basic arguments in this research field.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Armut; Einkommen; Export; Gemüse; Senegal; EU-Staaten; Schätzung